2000
DOI: 10.1086/313403
|View full text |Cite
|
Sign up to set email alerts
|

Very Long Baseline Polarimetry of BL Lacertae

Abstract: We present the results of an extensive observing campaign designed to study the evolution of parsecscale radio structure in the nucleus of the AGN galaxy BL Lacertae. The observations spanned 17 epochs from 1994.7 to 1998.3. The VLBA observations, made at regular intervals at 15, 22, and 43 GHz, show the ejection and evolution of four highly polarized superluminal components (denoted S7ÈS10). The trajectories of all components were signiÐcantly curved, with the slowest component (S8) exhibiting the most bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 32 publications
7
93
0
Order By: Relevance
“…This type of behaviour (predominance of longitudinal polarization at larger distances) is seen in some cases (Denn et al 2000;Gabuzda & Gómez 2001).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 79%
“…This type of behaviour (predominance of longitudinal polarization at larger distances) is seen in some cases (Denn et al 2000;Gabuzda & Gómez 2001).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 79%
“…For BL Lac this direction (θ = 114 • ) is nearly orthogonal to the direction of the movement of VLBI components in the 1980s, 188 • −196 • (Mutel et al 1990). Furthermore, the magnetic field is even closer to perpendicular to the jet axis on 1-2 milliarsecond scales of 195 • −206 • (Denn et al 2000) as one can expect if the optical radiation arises in shocks in the jet relatively close to the central engine (Marscher & Gear 1985). Such behaviour of the polarization at radio wavelengths is not unusual and can be explained by models involving transverse shocks moving along the jet (Hughes et al 1985).…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, VLBA/VLBI studies of the jet structure in AGNs have revealed bent jet morphologies that are suggestive of streaming motions along a helical path (see e.g. Lister 2001) or that the magnetic field may present a helical geometry (Gabuzda et al 2004); this is also true for BL Lacertae (Tateyama et al 1998;Denn et al 2000;Marscher et al 2008;O'Sullivan & Gabuzda 2009, see also Stirling et al 2003). Moreover, a rotating helical path in a curved jet was invoked by Villata et al (2009) to explain the optical and radio behaviour of BL Lacertae in the last forty years, in particular the alternation of enhanced and suppressed optical activity, accompanied by hard and soft radio events, respectively.…”
Section: Discussionmentioning
confidence: 97%